Interaksi Sosial Peserta Didik Atlet dengan Peserta Didik Reguler di SMA Widya Gama Malang dalam Kajian Teori Interaksionisme Simbolik George Herbert Mead - Dhuhita, Chandramaya Aulia; Mahbubah, Imarotul; Ristanti, Nadya Restu; Rosyidah, Ainur; Bustami, Abdul Latif (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2024)
This research aims to find out the process of social interaction between student athletes and regular students at SMA Widya Gama Malang, as well as how to overcome social problems in mixed classes of student athletes and regular students. Because researchers want to know the nature of social interactions formed between athlete students and regular students, who of course have different backgrounds and characteristics. This research uses a qualitative approach with a narrative research design. The theory used in this research is the theory of symbolic interactionism by George Herbert Mead, which holds that individuals form meaning through the communication process. This means that humans act towards other humans based on the meaning resulting from their communication process. This theory is also studied through three main concepts, namely Mind, Self, and Society. The results of this research show that the forms of social interaction carried out by the two types of students are influenced by the situations and conditions that occur in the field. Because not all ASIFA students have a character that is open to friends outside of fellow ASIFA athletes.